Clinical efficacy of acupuncture for diminished ovarian reserve: a systematic review and meta-analysis of randomized controlled trials - Lin, Guangyao; Liu, Xiyu; Cong, Chao; Chen, Siru; Xu, Lianwei (Frontiers in Endocrinology, 2023)
Objective: To evaluate the clinical efficacy of acupuncture for the treatment of diminished ovarian reserve (DOR) based on the existing randomized controlled trials (RCTs). Methods: Nine databases from their inception to December 6th, 2022, were comprehensively searched to retrieve RCTs related to the clinical efficacy of acupuncture for the treatment of DOR. The outcomes of interest were sex hormones level and antral follicle count (AFC). Risk of Bias (RoB) was adopted to assess the quality of the included trials. Results: A total of 13 RCTs involving 787 patients were included in this meta-analysis. The review of available evidence revealed acupuncture produced a significant efficacy in decreasing follicle-stimulating hormone (FSH) levels (SMD = -1.07, 95%CI [-1.79, -0.36], p = 0.003), FSH/LH ratio (MD = -0.31, 95%CI [-0.54, -0.09], p = 0.006) and increasing anti-Müllerian hormone (AMH) levels (SMD = 0.25, 95%CI [-0.00, 0.49], p = 0.05), along with AFC (MD = 1.87, 95%CI [0.96, 2.79], p < 0.0001) compared to controls. Compared with electro-acupuncture treatment, manual acupuncture was superior in reducing FSH levels, FSH/LH ratio, and increasing AMH levels and AFC (p < 0.05). A notable association was also seen when acupuncture was combined with traditional Chinese medicine therapy for improving FSH levels, FSH/LH ratio, and AFC (p < 0.05). Besides, a high dose of acupuncture (≥10 acupoints) was more conducive to improving FSH levels, FSH/LH ratio, and AFC (p < 0.05) than a low dose of acupuncture (＜10 acupoints). Substantial heterogeneity existed among studies. Conclusions: Acupuncture may have significant clinical potential for patients with DOR in terms of improving sex hormones level and increasing AFC, although the evidence is drawn with high heterogeneity. This finding suggests that more rigorous trials conducted in diverse regions worldwide are necessary to identify the efficacy of acupuncture for patients diagnosed with DOR.